FY2018 Uganda Country Opinion Survey Report - World Bank Group (World Bank, Washington, DC, 2019)
The Country Opinion Survey in Uganda assists the World Bank Group (WBG) in gaining a better understanding of how stakeholders in Uganda perceive the WBG. It provides the WBG with systematic feedback from national and local governments, multilateral/bilateral agencies, media, academia, the private sector, and civil society in Uganda on 1) their views regarding the general environment in Uganda. 2) their overall attitudes toward the WBG in Uganda. 3) overall impressions of the WBG’s effectiveness and results, knowledge work and activities, and communication and information sharing in Uganda; and 4) their perceptions of the WBG’s future role in Uganda.